Shakespeare and Digital Pedagogy: Case Studies and Strategies - Henderson, Diana E.; Vitale, Kyle Sebastian (Bloomsbury Publishing Plc, 2022)
Shakespeare and Digital Pedagogy is an international collection of fresh digital approaches for teaching Shakespeare. It describes 15 methodologies, resources and tools recently developed, updated and used by a diverse range of contributors in Great Britain, Australia, Asia and the United States. Contributors explore how these digital resources meet classroom needs and help facilitate conversations about academic literacy, race and identity, local and global cultures, performance and interdisciplinary thought. Chapters describe each case study in depth, recounting needs, collaborations and challenges during design, as well as sharing effective classroom uses and offering accessible, usable content for both teachers and learners. The book will appeal to a broad range of readers. College and high school instructors will find a rich trove of usable teaching content and suggestions for mounting digital units in the classroom, while digital humanities and education specialists will find a snapshot of and theories about the field itself. With access to exciting new content from local archives and global networks, the collection aids teaching, research and reflection on Shakespeare for the 21st century.